Testing hydrologic performance standards to evaluate wetland restoration - Sueltenfuss, Jeremy Paul, author; Cooper, David J., advisor; Ocheltree, Troy, committee member; Paschke, Mark, committee member; Rocca, Monique, committee member; Sanderson, John, committee member (Colorado State University. Libraries, 2018)
Defining success in wetland restoration can be difficult and subjective, as each restoration project has distinct goals. When wetland restoration projects fail to achieve their identified goals, it is often due to inadequately restored water levels. Incorrect water levels can lead to invasion by exotic species, or can alter the type of wetland that was supposed to be restored. To provide guidance to local wetland restoration efforts I investigated the hydrologic niche of Carex pellita, a wet meadow species commonly planted in wetland restoration, along with Typha latifolia, a species of cattail which commonly invades restored sites. Restored wetlands often have higher water levels than naturally occurring wetlands, and the prevailing assumption has been that hydrologic conditions in restored wetlands are not suitable for this species of Carex. Using experimental transplants across a hydrologic gradient, I found that Carex has a much wider hydrologic niche than previously thought. It produced either the same or more biomass in the high water level transplant treatment than in the low water level control plot. Typha responded negatively to being transplanted into areas with lower water levels. My results indicate Typha have filled their entire hydrologic niche in these wetlands and have competitively excluded Carex pellita to a smaller portion of its potential distribution. I also evaluated existing hydrologic and vegetation datasets from regulatory wetland restoration projects across the United States to help inform the development of wetland mitigation policy. The objective of regulatory wetland mitigation is to restore or create wetlands to offset the losses of wetland acreage and function incurred from impacts to existing wetlands. Unfortunately, wetland acreage and function are not always successfully replaced, and performance standards are now used in hopes to improve wetland mitigation outcomes. Because of the agreement in the scientific literature about the role of hydrology in creating and maintaining wetland structure and function, hydrologic performance standards may be an ecologically meaningful way to evaluate restoration outcomes. However, a framework for hydrologic performance standards has not been created or tested to date. I analyzed existing datasets from past and ongoing wetland mitigation projects to identify the number of years it took water levels in restored wetlands to match reference sites, and to test whether similar water levels between restored and reference sites leads to higher cover of native species. Wetland types differed in the number of years it took for water levels to match reference sites. Vernal pools in California took nine years to match reference sites, fens and wet meadows in Colorado took four years, and forested wetlands in the southeastern US were hydrologically similar to reference sites the first year following restoration. Plant species cover in all three restored wetland types was related to the water level similarity to reference sites. Native cover was higher when water levels were more similar to reference sites in some vernal pools, fens, and wet meadows, and was lower in areas where water levels were different. Exotic species cover showed the opposite relationship in fens and wet meadows, where hydrologic similarity led to low cover of exotic species. Forested wetlands showed no consistent relationship between tree seedlings or species richness and hydrologic similarity with reference sites. Based on the general agreement of the importance of hydrology for wetland form and function, hydrologic performance standards should be used in wetland mitigation. My research shows that hydrologic performance standards may also lead to increased vegetation success in some wetland types.
Keywords: mitigation; restoration; ecohydrology; wetlands; performance standards